2018
DOI: 10.1111/ijlh.12944
|View full text |Cite
|
Sign up to set email alerts
|

A level‐headed approach to measuring direct oral anticoagulants: A 2‐year retrospective analysis of DOAC levels from a tertiary UK centre

Abstract: Introduction Direct oral anticoagulants (DOAC) are commonly prescribed and measuring drug levels may be useful in a number of contexts. However, data on DOAC level measurement and their clinical utility in real‐world studies are limited. Methods We carried out a 2‐year retrospective cohort study of DOAC levels measured at our institution. Results One hundred and sixty‐nine levels measured in 113 patients were included in the final analysis. Our patients had a median age of 69.9. AF was the commonest indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
6
0
3
Order By: Relevance
“…Recent studies with more dynamic patient populations have noted higher interindividual variability in anti-Xa levels at any given time point, which further challenges the need for established therapeutic ranges. 48,49 Though our study findings explore potential use of anti-Xa level monitoring for safe anticoagulation practices in the interim, they are not intended to suggest deviation from current guideline-based clinical practice. More data is needed as challenges remain with anti-Xa level interpretation and subsequent long-term clinical-decision making.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies with more dynamic patient populations have noted higher interindividual variability in anti-Xa levels at any given time point, which further challenges the need for established therapeutic ranges. 48,49 Though our study findings explore potential use of anti-Xa level monitoring for safe anticoagulation practices in the interim, they are not intended to suggest deviation from current guideline-based clinical practice. More data is needed as challenges remain with anti-Xa level interpretation and subsequent long-term clinical-decision making.…”
Section: Discussionmentioning
confidence: 97%
“…Second, the action of ACs/APs would have persisted even when the AC was discontinued. Two studies 15,16 reported residual serum concentrations of ACs/ APs in patients who underwent elective invasive procedures. Anne et al 15 confirmed persistent AC effects in most patients even after discontinuing for 3 times the half-life of the known AC.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the anticoagulant action would have persisted even when the anticoagulant was discontinued. Two studies [16,17] reported residual serum concentrations of anticoagulants in patients who underwent elective invasive procedures. Anne et al [16] con rmed persistent anticoagulant effects in most patients even after discontinuing for 3 times the halflife of the known anticoagulant.…”
Section: Discussionmentioning
confidence: 99%